One industry, different conflicts: A typology of mining mobilization - Paredes, M. (Elsevier, 2022)
Mining conflicts are comprised of diverse socio-territorial mobilizations that originate in different parts of countries where mineral deposits are exploited, and became politicized to target international companies and national state policies. To analyze the diversity of mining conflicts, this paper develops a multidimensional matrix typology based on the intersection of two core dimensions: the framing of claims and the degree of disruption of repertoires of contention. The result is four types of conflicts: resistance, negotiation, subordination, and dependency. The paper finds empirical evidence for the conceptual typology through the analysis of a database of 49 case studies of mining conflicts in Latin America, providing rich, contextual, and historical information that allows not only for more accurate classifications of conflicts, but also for better understanding of how different combinations of claims and repertoires can advocate for different policy outcomes and relations with the state and mining companies.
Keywords: Repertoires of Contention; Multidimensional Typology; https://purl.org/pe-repo/ocde/ford#5.06.01